KORELASI ANTARA CBR, PI DAN KUAT GESER TANAH LEMPUNG - Purnomo, Mego (Semarang State University, 2011)
Abstract: In a practical planning sometimes does not need to do a soil test as a whole. Therefore requiresÃÂ anÃÂ approachÃÂ fromÃÂ theÃÂ soilÃÂ properties.ÃÂ ToÃÂ obtainÃÂ anÃÂ approachÃÂ tersebutperluÃÂ holdingÃÂ of repeated experiments in the laboratory, so it can be described in a graphical form of the elationship between naturesifaatÃÂ land. From garfikÃÂ if one ofÃÂ theÃÂ factorsÃÂ / characteristics are knownÃÂ thenÃÂ the other properties can be determined. This study used clay fromÃÂ the site PucangÃÂ Ivoire (Semarang), JalanÃÂ PedurunganGenukÃÂ (Semarang),ÃÂ KarangawenÃÂ (Demak),ÃÂ HutÃÂ (Purwodadi),ÃÂ Godong (Purwodadi).ÃÂ AndÃÂ conductedÃÂ researchÃÂ inÃÂ soilÃÂ mechanicsÃÂ laboratory.ÃÂ FromÃÂ theÃÂ researchÃÂ results obtained byÃÂ theÃÂ relationship between CBR and PIÃÂ is PI = 137.866.792 CBR and PI = 90.796ÃÂ to 4.574 CBR, CBR at an angle with the shear angle in the ground: ÃÂ¤ = 18.379 + 1.155 CBR and 1.71 ÃÂ¤ = 10.496 + CBR , CBR connection and cohesion, namely: CBR C = 0.165 0.279 and C = 0.174 CBR 0.5996, and PI relationship with the land gesr angle ÃÂ¤ = 49.9160.4 PI Keywords: Plastic Index, California Bearing Ratio, Strength Scroll, Clay Soil ÃÂ Abstrak: Dalam suatu perencanaan praktis kadang tidak perlu melakukan percobaan tanah secara keseluruhan. Oleh karena itu membutuhkan suatu pendekatan dari sifat,sifat tanah tersebut. Untuk memperolehÃÂ suatuÃÂ pendekatanÃÂ tersebutperluÃÂ diadakannyaÃÂ percobaanÃÂ yangÃÂ berulang,ulangÃÂ di laboratorium, sehingga dapat digambarkan dalam suatu bentuk grafis hubungan antara sifat,sifaat tanah tersebut. Dari garfik tersebut jika salah satu faktor /sifat diketahui maka dapat ditentukan sifat yangÃÂ lain.ÃÂ PenelitianÃÂ iniÃÂ menggunakanÃÂ tanahÃÂ lempungÃÂ dariÃÂ lokasiÃÂ PucangÃÂ GadingÃÂ (Semarang), JalanÃÂ Pedurungan,GenukÃÂ (Semarang),ÃÂ KarangawenÃÂ (Demak),ÃÂ GubukÃÂ (Purwodadi),ÃÂ Godong (Purwodadi).ÃÂ DanÃÂ penelitianÃÂ dilakukanÃÂ diÃÂ laboratoriumÃÂ mekanikaÃÂ tanah.ÃÂ DariÃÂ hasilÃÂ penelitian diperolehÃÂ hubunganÃÂ antaraÃÂ CBRÃÂ danÃÂ PIÃÂ yaituÃÂ PIÃÂ =ÃÂ 137,86 ÃÂ Ã¢â¬âÃÂ 6,792CBRÃÂ danÃÂ PIÃÂ =90,796ÃÂ Ã¢â¬â 4,574CBR, CBR dengan sudut dengan sudut geserÃÂ tanah dalam yaituÃÂ : ÃÂ¤ = 18,379 + 1,155CBR dan ÃÂ¤=10,496 + 1,71CBR, hubunganÃÂ ÃÂ CBR dan kohesi yaituÃÂ : C = 0,165 CBR Ã¢â¬â 0,279 dan C = 0,174CBR Ã¢â¬â 0,5996, dan Hubungan PI dengan sudut gesr tanah dalam ÃÂ¤ = 49,916 Ã¢â¬â 0,4PI Kata kunci: Plastik Indek, California Bearing Ratio, Kuat Geser, Tanah Lempung